PENANGGULANGAN TINDAK PIDANA VANDALISME - Arwin Iqbal Fauzan (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2024)
A The rise of criminal acts of vandalism in Surakarta makes the environment seem dirty and creates visual pollution. Regulations regarding acts of vandalism are listed in Article 62 letter l of Surakarta Regional Regulation Number 10 of 2015. The purpose of writing this article is to link sanctions and efforts to deal with acts of vandalism by law enforcement so that acts of vandalism can be reduced. The research methodology in this article is to analyze secondary data which is then followed by primary data. Primary data was obtained through observation and interviews, while secondary data was data obtained through literature study. Countermeasures related to vandalism by law enforcement officials are repressive and preventive efforts .